CUSUM Algorithms for Parameter Estimation in Queueing Systems with Jump Intensity of the Arrival Process; Communications in Computer and Information Science; Vol. 564 : Information Technologies and Mathematical Modelling - Queueing Theory and Applications - Burkatovskaya Yu. B. Yuliya Borisovna (2015, 2015)
Title screen